On the improvement of executive functions via a group-based intervention program : a preliminary analysis. - Shonata, Annesha. (2013)
Executive functions (EFs) are crucial cognitive processes that regulate children’s behaviors. In the present study, a group-based integrative EFs intervention program was developed for preschoolers. To test the effectiveness of this program, forty-four Singaporean preschoolers (M = 52.70; SD = 3.67; 19 girls) were recruited and assigned to either intervention or control condition. Measurements on the three components of EF including inhibitory control, cognitive flexibility, and updating, as well as the general EFs ability, were given before and after the intervention. Separate 2 testing time (pre-test/post-test) X 2 conditions (intervention/control) repeated measure Analysis of Variance (ANOVA) were conducted. Age-improvement from pre-test to post-test was found in all measures, except for inhibitory control. An interaction effect between testing time and conditions on the measure of cognitive flexibility was found, indicating that the intervention program improved flexibility in preschoolers.